The Christian Sabbath: Is It of Divine Origin? - Remsburg, John E. (John Eleazer), 1848-1919 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Christian Sabbath: Is It of Divine Origin?" by John E. Remsburg is a theological critique written in the late 19th century. This book presents an argument against the divine basis of the Christian Sabbath, asserting that Sunday lacks any more sanctity than any other day. Remsburg posits that the observance of Sunday as a holy day originated from pagan traditions rather than divine instruction, challenging the historical and ecclesiastical justifications for its significance within Christianity. In the text, Remsburg meticulously examines biblical references and historical statements from prominent Christian figures, including St. Paul, early church fathers, and key reformers. He argues that these works illustrate a consensus that the Sabbath has no binding authority under Christian doctrine. Each quoted authority reinforces his claim that Christians are not mandated to observe a specific day of rest, disputing the widely held belief that the shift from the Jewish Sabbath to Sunday was divinely ordained. The book unfolds as a detailed exploration of the cultural and theological misinterpretations surrounding Sabbath observance, ultimately advocating for a reconsideration of its significance in light of historical evidence. (This is an automatically generated summary.)
Release date is 2011-12-22
Produced by David Widger
Keywords: Sabbath